Immunity status against poliomyelitis in young migrants: a seroprevalence study - Veronesi, Licia; Colucci, Maria Eugenia; Capobianco, Emanuela; Bracchi, Maria Teresa; Zoni, Roberta; Palandri, Lucia; Affanni, Paola (Acta Biomedica Atenei Parmensis, 2019)
Background and aim of the work: Recent seroprevalence studies in different population groups have shown low antibody titers against poliomyelitis, especially in young adults. This, together with the reduction of vaccination rates, could favor the reintroduction of poliovirus in long-time polio-free countries. Within the Surveillance system of acute flaccid paralysis, a prevalence study was conducted to estimate the immunological status associated with poliomyelitis in young migrants. Methods: Local Health Authority collected serum samples in young migrants, without vaccination documentation. Antibodies levels were assessed with a long incubation neutralization assay. Subjects were stratified by age and by WHO region. Seroprotection was defined by a titer equal or above 1:8 and titers > 1:2 were log-transformed and evaluated as geometric mean titers (GMTs). Results: From January 2004 to August 2017, 1138 blood samples were collected. Mean age was 13.3 years with no differences between WHO regions. The percentage of antibody titers below 1:8 was 6.0% versus poliovirus 1 (PV1), 7.7% versus poliovirus 2 (PV2) and 15% versus poliovirus 3 (PV3). The GMTs were 45.5, 29.5 and 20 towards PV1, PV2 and PV3 respectively. In each WHO region, the GMTs towards PV3 were consistently the lowest, and the Europeans showed the lowest GMTs both towards PV2 and PV3 (27.5 and 15.3 respectively). GMTs decreased with age. Conclusion: The low GMTs and the clear tendency to decrease with increasing age of the subjects, especially against to PV1, confirm the framework of attention that polio is receiving at national and international level.